Answer:
40
Step-by-step explanation:
(6 + 2i)(6 - 2i)=40
Answer:
see below
Step-by-step explanation:
The exponent rules that apply are ...
(a^b)(a^c) = a^(b+c)
a^-b = (1/a)^b
(a^b)^c = a^(b·c)
_____
These let you rewrite the given function as ...
f(x) = (3^(2x))(3^1) = 3(3^(2x)) = 3(3^2)^x = 3·9^x
and
f(x) = 3^(2x+1) = (3^-1)^(-(2x+1)) = (1/3)^-(2x+1)
Answer:
- ∠R = 56°
- ∠Q = 90°
- ∠S = 34°
Step-by-step explanation:
The given triangle is a right angled triangle.
So, the angles in the triangle are :
- 90°
- (2x + 38)°
- (5x - 11)°
Solving according to <u>angle sum property</u>,
Sum of all angles in a triangle is 180°
90° + (2x + 38)° + (5x - 11)° = 180°
117° + 7x = 180°
7x = 180° - 117°
7x = 63°
x = 9
Angles =
2(9) + 38
56°
5(9) - 11
34°
- ∠R = 56°
- ∠Q = 90°
- ∠S = 34°
The angles are 56°, 90° and 34°.
Answer:
![x= -2, -1, 0, 1, 2\\y= 12, 4,0,0,4](https://tex.z-dn.net/?f=x%3D%20-2%2C%20-1%2C%200%2C%201%2C%202%5C%5Cy%3D%2012%2C%204%2C0%2C0%2C4)
Step-by-step explanation:
let me know if this is right please :(
A- It will be smaller, because we're finding a part of a number, and it's no more than 100 percent.
B- It would be greater. It's more than 100 percent, which accounts for the whole value, and goes even more.
Hope this helps!